Cost optimal urban energy systems planning in the context of national energy policies: A case study for the city of Basel. (November 2017) - Yazdanie, Mashael; Densing, Martin; Wokaun, Alexander
Abstract: With over 50% of the world's population residing in cities, urban areas have the potential to contribute significantly to global CO2 emissions reductions through careful urban energy systems planning and community participation. However, urban policymakers must operate within the constraints imposed by national energy policies. This study aims to understand the impacts of different national energy strategies on long-term urban energy systems planning through a case study for the city of Basel in Switzerland. A cost optimization modeling approach is employed and heat and electricity demand sectors are considered. Energy efficiency measures, particularly building renovations, are found to be cost optimal and enable significant energy demand reductions. Decentralized generation and storage technologies, including rooftop PV, heat pumps, small gas CHPs, and batteries, also provide pathways to reduce emissions and improve energetic self-sufficiency in the long-term. Heat generation using municipal waste provides a cost optimal, low emissions generation pathway as well. Carbon taxes are found to have a significant impact on the uptake of low-emission technologies. The urban environment encourages policymakers to pursue strategies to reduce local CO2 emissions across all national energy policy options evaluated, not only achieving, but also exceeding relative national policy targets in a cost optimal solution. Highlights: Study of cost optimal urban energy systems planning under national energy policies. Waste-fueled heat plants, heat pumps and PV form significant part of the energy mix. National CO2 pricing effective in reducing emissions via low-emission technologies. Renovations and energy efficient devices vital for reducing urban energy demand. PV and battery storage provide protection against grid electricity cost variations.